PENGARUH TERPAAN BERITA #STOPBELIESKRIMAICE PADA MEDIA SOSIAL TWITTER TERHADAP CITRA PT ALPEN FOOD INDUSTRY (AICE) (Survei Terhadap Mahasiswa Ilmu Komunikasi UPN Veteran Jakarta) - Tio Anggiting Tyas, (2021)
Information dissemination carried out by each individual in the industrial era 4.0 is growing not only through conventional media such as television, radio and newspapers but information can be easily accessed through social media. One of the social media used to find information is Twitter. Twitter makes it easy for its users to access information by using hashtags to view the news that is currently being discussed. The case of #StopBeliEsKrimAice has been widely discussed on Twitter regarding cases of demonstrations of company injustice against workers during 2020. This has caused many pros and cons to discussing this case on Twitter so that it became a trending topic during 2020. So starting from these problems, the purpose of the research This is to see if there is an influence and how much influence is the result of the #StopBeliEsKrimAice news circulating on Twitter on the image of PT Alpen Food Industry (Aice). The theory used in this research is image theory. This study uses quantitative research methods with probability sampling technique and the type of technique is propotionate stratified random sampling. The conclusion of this study is that there is an effect of exposure to the news #StopBeliEsKrimAice on the image of PT Alpen Food Industry (Aice) with a magnitude of 29.2%, which means there is an effect but the significance is small. And the suggestion in this research is that it is hoped that PT Alpen Food Industry can solve the problems of this case by paying attention to the welfare of its employees in order to build a positive image in the minds of employees or the Indonesian people.